The Effect Of Performance Contract Implementation On The Commitment Of Civil Servants At The Office Of Environmental Impacts Control And Mining In The Regional Mining Of Sinjai District Sulawesi Selatan - Saad, Hendra; Sumardi, Sumardi; Aswan, Andi (SEIKO : Journal of Management & Business, 2023)
This research aims to: 1)analyze the positive and significant impact of all performance contract variables for together through employee commitment, and 2) analyze the most dominant performance contract variables through employee commitment.The analytical method used is Multiple Regression with F test and t test tools. The results show that: 1)all performance contract variables impact for together through employee commitment , 2) for the four performance contract variables, quality improvement and information access of natural sources and environment is the most dominant through employee commitment, and 3) The most dominant variables influenced with employee commitment from the highest score to the lowest is X4, X3, X1, and X2 Keywords: Employee commitment, performance contract